Pembuatan Sistem Informasi Keuangan pada Tempat Wisata Twin Lake di Desa Kemangi Bungah Gresik - Saffana Assani'; Nur Abidin; Ade Hendi; Muhammad Izzuddin; Ahmad Nadhif Muhajir (Jurnal Pemberdayaan Masyarakat, 2022)
Twin Lake Tourist Attractions still carry out all of their business activities manually. Recording of financial transactions, data storage, and making transaction reports, are still done manually. This situation raises several problems, including requiring large data storage areas and requiring a relatively long time to generate transaction reports. By using a computerized information system, these problems can be solved. A financial information system is urgently needed because in addition to solving these financial problems, it will also be used as the first system to initiate the computerization of other manual systems at Twin Lakes Tourist Attractions. The information system developed uses the SDLC (system development life cycle) system development methodology, by creating functional and non-functional analysis documents as a design foundation using data flow diagrams (DFD) and development will be carried out using a web-based programming language. The result of this community service is in the form of an integrated financial information system that can be used to solve the problems experienced by the Twin Lakes Tourist Attractions. The information system will then be continued to be made into an integrated system with other systems, according to the needs of the Twin Lake Tourist Attractions.